High Body Mass Index Is Associated with an Increased Risk of the Onset and Severity of Ossification of Spinal Ligaments - Zhao, Yongzhao; Xiang, Qian; Lin, Jialiang; Jiang, Shuai; Li, Weishi (Frontiers in Surgery, 2022)
Background: Ossification of posterior longitudinal ligament (OPLL) and ligamentum flavum (OLF) are main types of the ossification of spinal ligaments (OSL) that cause the myelopathy. Although several studies have investigated the relationship of body mass index (BMI) with the onset or severity of OSL, it remains unverified because of the contradictory results of existing evidence. A systematic review and meta-analysis was performed in this work to determine the relationship of BMI with the onset and severity of the OSL. Methods: PubMed, EMBASE, Web of Science, and Cochrane Library were searched online for relevant studies focusing on the relationship of BMI with the onset or severity of the OSL. The difference in BMI of OSL (or severe OSL group) and non-OSL (or non-severe OSL group) groups was evaluated using the mean difference (MD) with a corresponding 95% confidence interval (CI). Results: Fifteen studies were included in this systematic review and meta-analysis. The BMI of the OSL group was significantly higher than that of the non-OSL group (MD = 1.70 kg/m2, 95% CI = 1.02–2.39 kg/m2, and P < 0.01). Similar results were observed in the subgroup analysis of female (P < 0.01), OPLL (P < 0.01), and OLF (P < 0.01) populations. Three studies reported a significant association of BMI with ossification index of OSL and standardized regression coefficient ranging from 0.11 to 0.43 (P < 0.05). Moreover, a significantly higher BMI was observed in the severe OSL group compared with that in the non-severe OSL group (MD = 3.09, 95% CI, 0.22–5.97 kg/m2, and P = 0.04). Conclusion: The significant association of high BMI with the onset and severity of the OSL may provide new evidence and insights into the management of OSL.